No impact of KIR-ligand mismatch on allograft outcome in HLA-compatible kidney transplantation - Tran, Thuong Hien; Unterrainer, Christian; Fiedler, Gerd; Döhler, Bernd; Scherer, Sabine; Ruhenstroth, Andrea; Adamek, Martina Maria; Middleton, D.; Opelz, Gerhard (American journal of transplantation, 2013)
Natural killer (NK) cell function can be modulated by the killer cell immunoglobulin-like receptors (KIR) which interact with human leukocyte antigen (HLA) class I molecules on target cells. KIR-ligand mismatching has recently been shown by van Bergen et al. (American Journal of Transplantation 2011; 11(9): 1959-1964) to be a significant risk factor for long-term graft loss in HLA-A, -B and -DR compatible kidney transplants. To verify this potentially important finding, we performed genotyping of 608 deceased-donor kidney graft recipients and their HLA-A, -B and -DR compatible donors for KIR and HLA, using samples and clinical data provided by the Collaborative Transplant Study. Graft survival of KIR-ligand-matched and -mismatched transplants was compared. We found no impact of KIR-ligand mismatching on 10-year graft survival in HLA-A, -B, -DR compatible kidney transplants. Further analysis did not reveal a significant effect of recipient activating/inhibitory KIR or KIR genotypes on graft survival. Our data do not support the concept that KIR-HLA matching might serve as a tool to improve long-term renal allograft survival.